Microbial fuel cells directly powering a microcomputer - Walter, Xavier Alexis (J Power Sources, 2020)
Many studies have demonstrated that microbial fuel cells (MFC) can be energy-positive systems and power various low power applications. However, to be employed as a low-level power source, MFC systems rely on energy management circuitry, used to increase voltage levels and act as energy buffers, thus delivering stable power outputs. But stability comes at a cost, one that needs to be kept minimal for the technology to be deployed into society. The present study reports, for the first time, the use of a MFC system that directly and continuously powered a small application without any electronic intermediary. A cascade comprising four membrane-less MFCs modules and producing an average of 62  mA at 2550 mV (158 mW) was used to directly power a microcomputer and its screen (Gameboy Color, Nintendo®). The polarisation experiment showed that the cascade produced 164 mA, at the minimum voltage required to run the microcomputer (ca. 1.850 V). As the microcomputer only needed ≈70 mA, the cascade ran at a higher voltage (2.550 V), thus, maintaining the individual modules at a high potential (>0.55 V). Running the system at these high potentials helped avoid cell reversal, thus delivering a stable level of energy without the support of any electronics.